A population study of tropical Peregrine Falcons (Falco peregrinus ernesti) in West Malaysia - Ooi, BengYean; Kéry, Marc; Percival, Robert; Lee, Zan Hui; Chiu, Sein Chiong (Zenodo, 2020)
Abstract The Peregrine Falcon ( Falco peregrinus ) is the most widely distributed bird species in the world, but very little is known about its tropical populations, where even very basic information (e.g. about population density) is mostly lacking. In January 2017, 2018 and 2019, we conducted three intensive surveys amounting to 27 days and 5,400 km driven by car in West Malaysia at latitudes between 3 and 7 °N, where the ernesti subspecies was confirmed to be a resident breeder only as recently as 1996. Here, we summarize our findings and combine them in a synthesis that includes all published and unpublished records of nesting peregrines that we could obtain in that area. In particular, we draw on the foundational work conducted by our late colleague Laurent Molard in 2003–2005. We give information about breeding habitats, local density, behavior and breeding phenology. We also describe and discuss our use of call playback during the surveys. Much more extensive reports for each survey, with plenty of photographs of all sites visited, are available upon request from the authors. According to current knowledge, Peregrines in West Malaysia nest mainly in cliffs, with some nesters on buildings exceptionally found (in Kuala Lumpur and suspected also elsewhere in cities) and possibly on large towers. Virtually all natural nesting places are limestone mountains with vertical cliffs. Owing to the mostly flat terrain in West Malaysia, with limestone cliffs only occurring very locally, the peregrine breeding distribution is extremely patchy. We found local aggregations in the regions of Ipoh (Perak), Gua Musang (Kelantan) and in the state of Perlis. However, local density is fairly low even in these hotspots, with nearest-neighbor distances in the densest cluster ranging from 3.7–5.6 km (mean 4.7). Overall, by the end of 2019, 36 occupied sites had been found in West Malaysia, of which 10 were known before 2003, 9 were found during the surveys by Mo-lard and his colleagues in 2003–2005, and 17 were new discoveries during our surveys in 2017–2019. In West Malaysia, the start of egg-laying appears to be late January and early February. We found playback of the ‘eeechup’ courtship calls to be extremely helpful when locating pairs. Playing a 26-sec sequence twice enticed the majority of birds to become airborne and/or to call, which greatly increased their detection probability and therefore survey success. In spite of the great increase in the number of known peregrine sites owing to our surveys, the currently known number of pairs is still considerably lower than the estimate by Molard et al. (2007) of 70–80 pairs. Although this latter may perhaps be a slight overestimate, we are convinced that many more pairs remain to be discovered in cliffs, where most of the future survey effort should be concentrated. This will then also provide the basic knowledge required to protect limestone outcrop sites, e.g. from quarrying activities, which may destroy entire limestone hills. However, we believe that the major uncertainty about the size of the population of nesting F. p. ernesti in Malaysia arguably comes from the population segment of nesters on buildings, which is likely underestimated and hard to survey and even discover in the first place. Moreover, given the rate of increase of nesters on buildings in other parts of the world, it is likely that the proportion of pairs nesting on buildings will increase also in Malaysia. Hence, we believe that new pairs will be discovered in the future also where there were none in earlier years.